2019
DOI: 10.1111/nph.16042
|View full text |Cite|
|
Sign up to set email alerts
|

Desiccation time during drought is highly predictable across species of Eucalyptus from contrasting climates

Abstract: Summary Catastrophic failure of the water transport pathway in trees is a principal mechanism of mortality during extreme drought. To be able to predict the probability of mortality at an individual and landscape scale we need knowledge of the time for plants to reach critical levels of hydraulic failure. We grew plants of eight species of Eucalyptus originating from contrasting climates before allowing a subset to dehydrate. We tested whether a trait‐based model of time to plant desiccation tcrit, from stom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 62 publications
(97 reference statements)
4
94
2
Order By: Relevance
“…However, as non-structural carbohydrates are fine-tuned (Choat et al, 2012;Bartlett et al, 2014;Delzon, 2015;Wang et al, 2018), synchronous seasonal changes in the embolism resistance traits of PS and TT lay a permanent foundation for hydraulic segmentation. The present study supported the HVSH and corroborated previous reports (Liu et al, 2015;Johnson et al, 2016;Blackman et al, 2019;Losso et al, 2019;Skelton et al, 2019). Strong segmentation among plant hydraulic traits between PS and TT could ensure year-round xylem functionality.…”
Section: Strong Segmentation Between Perennial Shoots and Terminal Twigssupporting
confidence: 92%
See 2 more Smart Citations
“…However, as non-structural carbohydrates are fine-tuned (Choat et al, 2012;Bartlett et al, 2014;Delzon, 2015;Wang et al, 2018), synchronous seasonal changes in the embolism resistance traits of PS and TT lay a permanent foundation for hydraulic segmentation. The present study supported the HVSH and corroborated previous reports (Liu et al, 2015;Johnson et al, 2016;Blackman et al, 2019;Losso et al, 2019;Skelton et al, 2019). Strong segmentation among plant hydraulic traits between PS and TT could ensure year-round xylem functionality.…”
Section: Strong Segmentation Between Perennial Shoots and Terminal Twigssupporting
confidence: 92%
“…Thus, the annual tradeoffs between hydraulic efficiency and safety traits are unclear, several traits may have tradeoffs while others may not, on the whole plant hydraulic traits, the tradeoffs are weak. No consistent results have been reported in previous studies (Liu et al, 2015;Johnson et al, 2016;Blackman et al, 2019;Losso et al, 2019;Skelton et al, 2019). In a global metaanalysis, only ∼1/4 of the studies reviewed supported the safety-efficiency hypothesis while the remaining 3/4 did not (Gleason et al, 2016).…”
Section: Weak Tradeoff Among Plant Hydraulic Traitsmentioning
confidence: 58%
See 1 more Smart Citation
“…The significantly greater P88 in HRI-D saplings indicates a capacity to tolerate a greater level of water stress during drought in comparison with saplings from other population × treatment combinations. In support of these findings, Blackman et al (2019b) found a strong relationship between P50 and the time for saplings to desiccate from stomatal closure (Pgs90) to P88 (tcrit) in eight Eucalyptus species, with those exhibiting greater stem P50…”
Section: Hydraulic and Allocation Traits Influencing Time To Hydraulimentioning
confidence: 52%
“…The eucalypts were sourced from a range of vegetation communities (wet sclerophyll forest, dry sclerophyll forest, grassy woodland and semiarid woodland). Further details of the study design and data were provided in Li et al [37], Li et al [38] and Blackman et al [39]. Images of the leaves of each species are provided in Figure S1.…”
Section: Common Garden Case Studymentioning
confidence: 99%